JIWA KEWIRAUSAHAAN MAHASISWA TEMPATAN (STUDI MAHASISWA BIDANG EKONOMI DI KOTA PEKANBARU) - UNILAK, Hadiyati; UNILAK, Bambang Suroto; UNILAK, Fatkhurahman; UNILAK, Nofrizal (Journal of Techno-Social, 2017)
Entrepreneurial spirit is perceived as the spirit, attitude, behaviour and ability of a person in dealing with a business or activity that leads to searching, creating and implementing new methods of working, technology and new products by increasing efficiency in order to provide better service and or gain greater profits. To what extent is the success implementing the entrepreneurship program by the Faculty of Economics will be examined by comparing the entrepreneurial spirit of the students in the first semester in this case is the second semester and comparing them with the entrepreneurial spirit of semester VIII. The method used in this research is survey by using questionnaire and the sample was taken using Proportionate sampling and analysed by using descriptive technique. The results showed that there is a significant difference in entrepreneurial spirit, which meansthat the research hypothesis is accepted, thus proving that through the learning process given on campus, it can provide some sortof changes in students’ entrepreneurship.